Conflict Weather: Climate Change as a Driver of Pastoralist Conflicts in the Lake Chad Region - Akinyetun, Tope Shola; Ogunbodede, Nife Elizabeth (Jurnal Politik, 2023)
The Lake Chad region hosts a significant portion of sub-Saharan Africa’s pastoralist activities. Pastoralism in the region has become synonymous with armed conflict, thus escalating the tension in the area and making it a hotbed of insecurity. Among other things, the exacerbation of the herder-farmer crisis in this area is attributable to climate change. Lake Chad which serves as a source of water, fodder, and fertile land for herders and farmers in the region, has been shrinking. This, coupled with drought, flooding, and variability in weather patterns, forces pastoralists to move around and engage in a constant migratory pattern, resulting in war-like competition for resources with farmers in the host communities. This paper adds to the debate on the role of climate change in fueling pastoralist conflicts in the area. The discourse, presented using qualitative methods and secondary data sourced from journal articles, briefs, reports, and internet sources, is couched using the political ecology framework. The paper finds that intensity of violent events and fatalities involving pastoralists in the area is driven by the disruption of livelihood occasioned by climate change. Four patterns of pastoralist conflict in the area are identified: conflict between herders and farmers; between different pastoralist groups; between the pastoralist and government; and between the pastoralist and other resource users. The paper also identifies the effects of climate change on displacement, disruption of economic activities, and undermining pastoralist livelihood.